(untitled) (Journal of Advanced Research in Social Sciences, 2025)
It is known that the contempt for authority by both indigenous peoples and Spaniards during the conquest and colonisation of America is a cause of political instability in Argentina. Contempt for authority can be quantified by measuring the level of non-compliance with laws and regulations, and indigenous or Spanish origins can be determined through genetic quantification. This study investigates the underlying mathematical relationships among legal and genetic variables without taking causality into account. Using genetic, legal, and geographical data from 24 Argentine provinces, significant correlations are identified between vertical fiscal imbalance, property tax evasion, and fatal traffic accident rates with Amerindian and African genetic content, excluding CABA. Unregistered work shows a high correlation with the latitudes of capital cities, probably due to the geographical and temporal sequence of Argentina’s colonisation. Multidimensional cluster analysis reveals three regions in Argentina with similar social behaviours based on genetic composition, law compliance, and geographical proximity. These findings highlight the complex interplay between genetic heritage and socio-legal dynamics, offering new insights into Argentina’s political instability.